Mediating American autobiography photography in Emerson, Thoreau, Douglass, and Whitman - Meehan, Sean Ross, 1969- (University of Missouri Press, 2008)
"Examines works by Ralph Waldo Emerson, Henry David Thoreau, Frederick Douglass, and Walt Whitman to explore how the emergence of photography in the mid-nineteenth century transformed their ideas, how photography mediated their conceptions of self-representation, and how their appropriation of photographic thinking created a new kind of autobiography"--Provided by publisher.